The effect of caffeic acid phenethyl ester and Ankaferd Blood Stopper on the diabetic and nondiabetic gingival wound healing: an experimental study - Gul, Mehmet; Dundar, Serkan; Artas, Gokhan; Yigin, Akin; Tanik, Abdulsamet; Polat, Mehmet Emrah; Ozcan, Erhan Cahit (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: Healthy wound healing is very important for patient comfort. Diabetes is one of the factors that negatively affect wound healing. Ankaferd Blood Stopper (ABS) and caffeic acid phenethyl ester (CAPE) are antiinflammatory and antimicrobial agents and may have positive effects on wound healing. Materials and methods: In this study, 72 male Wistar albino rats were used. Rats; control, CAPE, ABS, diabetes + control, diabetes + ABS and diabetes + CAPE groups were divided into 6 groups. A healthy 36 rats created diabetes using streptozotocin (STZ). A gingival wound was created using a 4-mm punch biopsy in the gingival tissue under the lower anterior incisors of the rats. Results: The comparison between the nondiabetic groups had a statistically significant positive effect compared to the control group of CAPE and ABS (P < 0.05). In the comparison between ABS and diabetes + ABS groups and in the comparison between CAPE and diabetes + CAPE groups, a decrease in vascularization in diabetes + CAPE groups was observed and it was statistically significant (P < 0.005). Conclusion: ABS and CAPE have been found to have positive effects on gingival wound healing in the nondiabetic group. We think that this situation is caused by its antiinflammatory and antimicrobial properties.
Keywords: Ankaferd Blood Stopper; caffeic acid phenethyl ester; diabetes; gingival wound healing